2017
DOI: 10.3892/mmr.2017.6266
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal differentiation of stem cells into enteroendocrine cells in rats with DSS-induced colitis

Abstract: The present study aimed to determine whether there is an association between abnormalities in enteroendocrine cells in dextran sulfate sodium (DSS)-induced colitis and the clonogenic and/or proliferative activities of stem cells. A total of 48 male Wistar rats were divided into four groups. Animals in the control group were provided with normal drinking water, whereas DSS colitis was induced in the remaining three groups. The rats with DSS-induced colitis were randomized into the following three groups: i) DSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 84 publications
2
8
0
Order By: Relevance
“…The mechanisms underlying the changes in ENS during inflammation in IBD remain unclear. However, recent studies have shed some light on the possible mechanisms of the inflammation-induced changes in the GI endocrine cells in IBD[ 258 , 270 ].…”
Section: Nes Nepa In Ibdmentioning
confidence: 99%
See 3 more Smart Citations
“…The mechanisms underlying the changes in ENS during inflammation in IBD remain unclear. However, recent studies have shed some light on the possible mechanisms of the inflammation-induced changes in the GI endocrine cells in IBD[ 258 , 270 ].…”
Section: Nes Nepa In Ibdmentioning
confidence: 99%
“…Abnormal stem cell clonogenic and differentiation activities: Each intestinal crypt contains four to six stem cells that either divide into identical new stem cells (clonogenic) or differentiate into all types of epithelial cells through a series of progenitors[ 270 - 281 ]. This differentiation into epithelial cells includes the secretory and absorptive lineages.…”
Section: Nes Nepa In Ibdmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanisms underlying such abnormalities are not yet known. However, a recent study using an animal model of human UC, namely dextran sulfate sodium-induced colitis, found that the abnormalities in enteroendocrine cells strongly correlated with the abnormal differentiation progeny of stem cells (25). It has been suggested that the abnormalities in the enteroendocrine cells in this animal model are caused by an abnormal stem cell differentiation progeny toward enteroendocrine cells (25).…”
Section: Introductionmentioning
confidence: 99%